Performance Sampling in Social Matches. - March, James C.; March, James G. (Administrative Science Quarterly)
Many social structures can be viewed as collections of interconnected voluntary social pairings, for example, matches between jobholders and jobs, husbands and wives, or residents and neighborhoods. A general performance sampling model is suggested as a framework for exploring how mutual evaluation within such matches affects their continuation, and thus the structure of matches involved. The model treats continuation in a pairing as a decision made under conditions of imperfect information. It emphasizes the sampling errors involved in using small samples of observations to form judgments about matches. There are indications that the sampling characteristics of the process will often be robust enough to obscure other effects. The specific implications of one version of the model are shown to agree well with general observations from social mobility studies and more specific data from Wisconsin school superintendents. The implications of performance sampling for understanding careers in organizations and social pairings more generally are discussed. In contrast to an earlier paper, which explored major features of the gross structure of matches between superintendencies and superintendents, the present paper looks at the fine structure of the ways in which individuals leave jobs. The attempt is both to illuminate how a particular system of careers might arise from a series of elementary decisions with respect to job exits, and to connect a theory of organizational careers more explicitly with theories of other social pairings.